Anticholestatic effects of bezafibrate in patients with primary biliary cirrhosis treated with ursodeoxycholic acid12. Issue 5 (5th April 2013) - Honda, Akira; Ikegami, Tadashi; Nakamuta, Makoto; Miyazaki, Teruo; Iwamoto, Junichi; Hirayama, Takeshi; Saito, Yoshifumi; Takikawa, Hajime; Imawari, Michio; Matsuzaki, Yasushi
Abstract: Bezafibrate is a widely used hypolipidemic agent and is known as a ligand of the peroxisome proliferator‐activated receptors (PPARs). Recently this agent has come to be recognized as a potential anticholestatic medicine for the treatment of primary biliary cirrhosis (PBC) that does not respond sufficiently to ursodeoxycholic acid (UDCA) monotherapy. The aim of this study was to explore the anticholestatic mechanisms of bezafibrate by analyzing serum lipid biomarkers in PBC patients and by cell‐based enzymatic and gene expression assays. Nineteen patients with early‐stage PBC and an incomplete biochemical response to UDCA (600 mg/day) monotherapy were treated with the same dose of UDCA plus bezafibrate (400 mg/day) for 3 months. In addition to the significant improvement of serum biliary enzymes, immunoglobulin M (IgM), cholesterol, and triglyceride concentrations in patients treated with bezafibrate, reduction of 7α‐hydroxy‐4‐cholesten‐3‐one (C4), a marker of bile acid synthesis, and increase of 4β‐hydroxycholesterol, a marker of CYP3A4/5 activity, were observed. In vitro experiments using human hepatoma cell lines demonstrated that bezafibrate controlled the target genes of PPARα, as well as those of the pregnane X receptor (PXR); down‐regulating CYP7A1, CYP27A1, and sinusoidal Na + /taurocholate cotransporting polypeptide (NTCP), and up‐regulating CYP3A4, canalicular multidrug resistance protein 3 (MDR3), MDR1, and multidrug resistance‐associated protein 2 (MRP2). Conclusion : Bezafibrate is a dual PPARs/PXR agonist with potent anticholestatic efficacy in early‐stage PBC patients with an incomplete biochemical response to UDCA monotherapy. (HEPATOLOGY 2013)